The destruction of republican modernity. (Un)reasons for the Spanish Pedagogical Exile - Fernandez Soria, Juan Manuel (Historia y Memoria de la Educación, 2019)
This text exposes the reasons that pushed thousands of Spanish teachers, inspectors, professors and scientists into internal and external exile, paying special attention to the so-called «pedagogical exile». Teachers and researchers sympathetic to the Republic felt condemned and threatened by the insurgents for combining a triple identity: that of republicans (the absolute enemy, «incarnation of evil»), that of intellectuals (foreigners and «poisoners of the popular soul»), and that of teachers («traitors to the fatherland», laymen and propagators of the republican creed). To this triple identity, unreasonable motive of exile, two more crucial factors influenced their decision to leave their land, their home and their homeland: their commitment to the modernization of Spain ―the primary object of the Francoist repressive mechanics― and the impossibility of being part of the pedagogy of the new Spain, which assumed as its principal objective the dismantling of republican education and the construction of a new one. This new education was to be based on the so-called «antithesis» represented by Francoist education, expressed in the second part of the binomials (public / private; universal / selected; lay / catholic; pacifist / combatant; pleasure / sacrifice; spontaneity / disciplinary; etc.) The result of exile and the substitution of one philosophical and pedagogical thought for another «new» one, is well known: the destruction of modern Spanish pedagogy.